Mitral valve replacement with Alvarez prosthesis: long-term results - Mashhour, Y. A. S. (1969)
The high mortality and morbidity that follow insertion of the Alvarez valve in the mitral position, and particularly the thrombo-embolic complications, stopped us from using it clinically in the Leeds General Infirmary.